Self-healing properties of carbon nanotube filled natural rubber/bromobutyl rubber blends - H. H. Le; S. Hait; A. Das; S. Wiessner; K. W. Stoeckelhuber; F. Boehme; Uta Reuter; K. Naskar; G. Heinrich; H.-J. Radusch (eXPRESS Polymer Letters, 2017)
In the present work, the development and characterization of an intrinsically self-healable material based on butyl imidazole modified bromobutyl rubber (BIIR)/natural rubber (NR) blends, which are filled with carbon nanotubes (CNTs) are reported. It was found that the addition of CNTs and the blending with NR significantly enhance the tensile strength of the BIIR composites. The use of butyl imidazole as physical cross-linker for the BIIR phase provides the blend composites the non-covalent bondings, which are responsible for their self-healing properties. Owing to the increase of the viscosity of the BIIR phase upon its physical crosslinking the island-matrix morphology of the blend changes over to a co-continuous structure. The preferential wetting of the CNT surface by the low-loading NR phase in the NR/BIIR blends can be explained by the good rubber-filler interaction between the linked phospholipids of the NR molecules and the π-electrons of the CNT surface. As a result, the favored localization of the CNTs in the NR phase strongly improves the electrical properties of the blends according to the double percolation theory. On the other hand it does not deteriorate the self-healing of the BIIR phase. The high electrical conductivity provides us a possibility to heat the blend by application of an electrical voltage in order to accelerate the self-healing process.